The Effectiveness of Scientific Learning Model Based on Local Wisdom of Kendal Batik on Learning Ability of Early Childhood Students - Sofiyah; Utomo, Slamet; Khamdun (Asian Journal of Assessment in Teaching and Learning, 2023)
The traditional learning model has proven suboptimal in terms of knowledge transfer absorbed by children within the first fifteen minutes of learning, especially when compared to the absorption of contextual understanding related to the real world. This model does not support children in developing critical, analytical, and precise thinking skills necessary for identifying, understanding, solving problems, and applying learning material. Therefore, there is a need for an appropriate learning development model tailored to child development. This research, a combination of research and development, aims to find practical model products suitable for use in the field of education. The research method consists of four stages: define, design, develop, and disseminate. Data analysis techniques include descriptive statistics and the N-Gain test, while data validity techniques involve both quantitative and qualitative data using concurrent triangulation. These data sets are then compared to identify convergence, differences, or combinations. The study concludes that the scientific learning model is suitable for use in Kindergarten B at PKG Markisa Kendal, effectively improving the cognitive abilities of early childhood students. This conclusion is supported by product trial results, indicating that the experimental class using the scientific model outperformed the control class using conventional learning models.